How Likely Is an Inflation Disaster? - Hilscher, Jens; Raviv, Alon; Reis, Ricardo (Review of Financial Studies, 2026)
Long-dated inflation swap contracts provide widely used estimates of expected inflation. We develop methods to estimate complementary tail probabilities for persistently very high or low inflation using inflation options prices. We show that three new adjustments to conventional methods are crucial: inflation, horizon, and risk. We find that: (a) U.S. deflation risk in 2011–2014 has been overstated, (b) ECB unconventional policies lowered deflation disaster probabilities, (c) inflation expectations deanchored in 2021–2022, (d) reanchored as policy tightened, (e) but the 2021–2024 disaster left scars, and (f) U.S. expectations are less sensitive to inflation realizations than in the eurozone.